A boatbuilder's approach to boat documentation. Issue 2 (1st September 2022) - Leijonhufvud, Fredrik
Documentation of historical objects is already included in established research areas, such as archaeology and conservation. From a craft perspective, studies of objects can contribute to the understanding and revitalization of broken craft traditions. In this article, I present a methodological approach for the documentation of craft objects, including a comparison of traditional analogue methods and modern digital photogrammetry. From a boatbuilder's perspective, I document traditional boats. In my current Ph.D. project, I investigate how documentation of objects, from a craftsperson's perspective, can be used to reconstruct craft processes. The case study is on the 'Öka' from the Stockholm archipelago, a local variation of the Nordic clinker boat tradition. In this article, I present the basic structure of my boat documentation work and pinpoint some specific examples of the use of digital methods, analogue measuring and documentation led by craft practice. A good practice of documentation needs to consider the advantages and shortcomings of analogue as well as digital methods and also integrate the craftsperson's perspective. Even if the craftsperson-researcher is skilled, artefacts have limitations as sources of craft knowledge, which must be taken into account in the interpretation process. An awareness of one's own traditions and prejudices is needed to interpret a boat built in an older tradition. The documentation should be guided by craft practice, deliberately focusing on questions that reconstruction work generates.